Kontribusi Petani Perempuan Dalam Proses Pertanian Padi di Desa Marampiau Kabupaten Tapin - Samsi, Muhammad; Damaiyanti, Varinia Pura; An’amta, Dimas Asto Aji (Huma: Jurnal Sosiologi, 2024)
Women in Marampiau Village play a role and contribute to the family's socio-economy by farming rice. This research aims to analyse the contribution of women farmers in the process of rice farming. The theories used in this research are women and development proposed by Mosse, as well as gender theory and women's marginalisation. This research uses a qualitative approach, with the type of field research. The research was conducted in Marampiau Village, Candi Laras Selatan District, Tapin Regency. Data collection techniques used observation, interviews and documentation. Data analysis techniques through the stages of data reduction, data presentation and conclusion drawing. The results show that women farmers in Marampiau Village generally do not experience discrimination. When they work in the fields, the portion they do will be the same as men, from the beginning of land clearing, seed sowing, rice planting to harvesting. Likewise, the wages received, both men and women receive the same amount of wages, namely 60 thousand to 65 thousand per day. Working in agriculture is an occupational choice that many women in Marampiau Village make. Apart from the favourable environmental conditions, the factor of their husbands working as farmers also encourages them to work to help their husbands. In this study, it can be concluded that in the Marampiau Village community there is no discrimination against women farmers, but a division of labour between women and men. Indeed, this research is expected to be able to deliver new knowledge that marginalisation does not always occur in a society. In farming families in Marampiau Village, what happens is the process of division of labour carried out to ease the family's economic burden.